Benefactive Verbs and Causative Verbs in Madurese: Morphosyntactic Analysis - Farda Naila Salsabila; Agus Subiyanto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study is aimed to analyze a morphological process in the marker of benefactive verbs and causative verbs construction of Madurese Language. The theory used in this study was of generative morphology and syntax. The object of this study was Madurese Language. The data collected in Madurese Language was from the native speakers of Madurese. The result of this research was the formation rules of benefactive verbs and causative verbs of Madurese Language by using word and paradigm approach. The results show that there were three kinds of affixation to produce the benefactive verbs. Affixation in the marker of benefactive verb was shown by prefixes a-, ma-, and n-, and suffix –aghi. Affixation in the marker of causative verb was shown by prefixes ma-. Madurese also use intransitive verb and also adjective as the root to construct benefactive verb and causative verb. Keyword: Benefactive Verbs, Causative Verbs, Generative Morphology, Madurese